2015
DOI: 10.1021/acs.joc.5b02308
|View full text |Cite
|
Sign up to set email alerts
|

P-Arylation of Dialkyl Phosphites and Secondary Phosphine Oxides with Arynes

Abstract: The novel P-arylation of dialkyl phosphites and secondary phosphine oxides with arynes has been achieved. The reactions produce dialkyl arylphosphonates in 71-99% yield and tertiary phosphine oxides in 68-92% yield under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 53 publications
4
17
0
Order By: Relevance
“…In this context, one successful approach relied on the nucleophilic addition of dialkyl phosphites to in situ generated arynes from 2-(trimethylsilyl)aryl triflates (Kobayashi precursors, Scheme 1a). 11 It has been also recently reported that the combination of diaryliodonium salts with phosphites can form an electron donor−acceptor complex, upon irradiation with blue light in the presence of a base, leading to the desired aryl phosphonates (Scheme 1b). 12 The photoinduced oxidation of arylhydrazines to produce aryl radicals that were trapped with trialkyl phosphites was also recently developed, 13 using an organic photocatalyst and 1,4-diazabicyclo[2.2.2]octane (DABCO) as an additive under aerobic conditions (Scheme 1c).…”
Section: ■ Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this context, one successful approach relied on the nucleophilic addition of dialkyl phosphites to in situ generated arynes from 2-(trimethylsilyl)aryl triflates (Kobayashi precursors, Scheme 1a). 11 It has been also recently reported that the combination of diaryliodonium salts with phosphites can form an electron donor−acceptor complex, upon irradiation with blue light in the presence of a base, leading to the desired aryl phosphonates (Scheme 1b). 12 The photoinduced oxidation of arylhydrazines to produce aryl radicals that were trapped with trialkyl phosphites was also recently developed, 13 using an organic photocatalyst and 1,4-diazabicyclo[2.2.2]octane (DABCO) as an additive under aerobic conditions (Scheme 1c).…”
Section: ■ Introductionmentioning
confidence: 94%
“…In addition, intensive efforts have been made recently in the development of TM-free synthesis of aryl phosphonates at room temperature. In this context, one successful approach relied on the nucleophilic addition of dialkyl phosphites to in situ generated arynes from 2-(trimethylsilyl)­aryl triflates (Kobayashi precursors, Scheme a) . It has been also recently reported that the combination of diaryliodonium salts with phosphites can form an electron donor–acceptor complex, upon irradiation with blue light in the presence of a base, leading to the desired aryl phosphonates (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
“…For substrates 6-25, the 31 P NMR shifts were in the range of 32.66-39.33 ppm, which was the typical range for aryldialkylphosphine sulfides [70,71]. The signal of aryldialkylphosphine oxides are usually found around 30-50 ppm [61,72,73], and hence the overlapping signals make this technique inappropriate for the analysis of the reaction products.…”
Section: Methodsmentioning
confidence: 99%
“…In 2016, Chen group reported the transition‐metal free P‐arylation reaction of arynes with dialkyl phosphites and secondary phosphine oxides (Scheme 25). [36] A set of arylphosphonates and tertiary phosphine oxides were obtained in moderate to high yields in the presence of CsF and Cs 2 CO 3 . The proposed reaction mechanism started with a Cs 2 CO 3 ‐assisted P(V)‐to‐P(III) tautomerization.…”
Section: Reactions Of Aryne With Organophosphorus(v) Compoundsmentioning
confidence: 99%